Evaluation of interactive computerized training to teach parents to implement photographic activity schedules with children with autism spectrum disorder. Issue 3 (28th March 2017) - Gerencser, Kristina R.; Higbee, Thomas S.; Akers, Jessica S.; Contreras, Bethany P.
Abstract : Training parents of children with autism spectrum disorder can be a challenge due to limited resources, time, and money. Interactive computerized training (ICT)—a self‐paced program that incorporates instructions, videos, and interactive questions—is one method professionals can use to disseminate trainings to broader populations. This study extends previous research on ICT by assessing the effect of ICT to teach three parents how to implement a photographic activity schedule using a systematic prompting procedure with their child. Following ICT, all parents increased their fidelity to implementation of an activity schedule during role‐play sessions with an adult. Fidelity remained high during implementation with their child and maintained during a 2‐week follow‐up.